Interaction of triosephosphate isomerase from the cell surface of Staphylococcus aureus and α-(1→3)-mannooligosaccharides derived from glucuronoxylomannan of Cryptococcus neoformans - Furuya, Hiromi (Microbiology Society, 2009)
The glycolytic enzyme triosephosphate isomerase (TPI; EC 5.3.1.1) of Staphylococcus aureus is a candidate adhesion molecule for the interaction between the bacterium and the fungal pathogen Cryptococcus neoformans. TPI may recognize the mannan backbone of glucuronoxylomannan (GXM) of C. neoformans. We purified TPI from extracts of S. aureus surface proteins to investigate its binding by surface plasmon resonance analysis. The immobilized TPI reacted with GXM in a dose-dependent manner. Furthermore, the interactions between staphylococcal TPI and α-(1→3)-mannooligosaccharides derived from GXM were examined. The oligosaccharides exhibited binding with TPI; however, monomeric mannose did not. Differences in the slopes of the sensorgrams were observed between oligosaccharides with an even number of residues versus those with an odd number. A heterogeneous ligand-parallel reaction model revealed the existence of at least two binding sites on TPI. The enzymic activities of TPI were inhibited in a dose-dependent manner by α-(1→3)-mannooligosaccharides larger than triose. The binding of TPI and α-(1→3)-mannotriose near the substrate-binding site was predicted in silico (AutoDock 3.05). An oligosaccharide of size equal to or greater than triose could bind to the site, affecting enzymic activities. Moreover, affinities were indicated, especially for biose and tetraose, to another binding pocket, which would not affect enzymic activity. These data suggest a novel role for TPI, in addition to glycolysis, on the surface of S. aureus.